Pengembangan Bahan Ajar Musik Vokal Berbasis Folk Song â€œSeu Aziâ€ Untuk Mendukung Proses Internalisasi Nilai-nilai Luhur Budaya Pada Mahasiswa/I STKIP Citra Bakti, Ngada, Flores, NTT (Universitas Negeri Semarang, 2020)
The purpose of this research is to develop a vocal music teaching material product based on the folk song (folk song) seu azi which is a folk song in the Ngada culture. This development research (R & D) follows the ADDIE research and development procedure which consists of 5 stages of teaching material development, namely 1) analyze, 2) design, 3) development, 4) implementation, and 5) evaluation. The results of this study were 1) the material expert trial obtained a score in good category (4.17), 2) lecturers who taught Vocals were also in the good category (3.88), and 3) students were in the very good category. (4.27), so that the average score is 4.10 (Good). Based on the results of these trials, teaching material developed is suitable for use by students of the Music Education Study Program, STKIP Citra devotion for Vocal Music Courses.